ASSESSMENT OF SEED QUALITY OF DIFFERENT CABBAGE LOTS DURING AGING - Poštić, Dobrivoj (Journal on Processing and Energy in Agriculture, 2022)
The aim of the research was to evaluate the influence of the year and the seed lots on the most important indicators of cabbage seed quality. Quality testing of nine different seed lots of Potomac F1 cabbage was performed during three years (2019, 2020 and 2021). Analyses of variance showed a significant effect (p